An Analysis on Obstacles to the Science Education Process - Cindy Dwi Kartini; Ika Chastanti; Dahrul Aman Harahap (Jurnal Penelitian Pendidikan IPA, 2022)
Numerous obstacles might arise throughout the process of science education. The obstacles in the science education process include a lack of concentration on the part of the students, a lack of understanding of the material, and the use of learning media. The aim of this study is to identify the obstacles to science education at the Private Vocational School of Al-Washliyah Silangkitang. Purposive sampling is used in this study. The researcher selects samples in accordance with the research goals, with the expectation that they address the researcher's concerns. The data analysis strategy was qualitative descriptive, utilizing the Miles and Huberman model. The results showed that the obstacles experienced during the science education learning process based on the highest percentage were indicators of the use of learning media by 69% and the students do not comprehend the teacher's information at 66.70%. The lowest percentage in the category of the students who are uninterested is 65.30% and students have difficulty concentrating in learning at 62.10%. In general, the results obtained from the questionnaire data show that the students' obstacles during the science education process have been on average 65.78%. Teachers and students stated that the difficulty in understanding science material was due to the lack of textbooks or handbooks. As a result, it requires an engaging learning environment and the availability of science textbooks